Exercise Protects Against Cognitive Injury and Inflammation in Alzheimer's Disease Through Elevating miR-148a-3p. (1st March 2023) - Chen, Jinli; Bai, Xiaojing; Wu, Quan; Chen, Lilong; Wang, Hui; Zhang, Jianfeng
Highlights: The level of miR-148a-3p in AD patients was lessened, while reversed after exercise. Detection of miR-148a-3p levels might distinguish AD patients from healthy humans. MiR-148a-3p levels were associated with cognitive ability and inflammatory response. Voluntary exercise might inhibit cognitive disability via regulating miR-148a-3p. MiR-148a-3p participated in the regulation of voluntary exercise on inflammation. Abstract: Alzheimer's disease (AD) is a chronic neurological disorder with high morbidity. Exercise is one of the effective ways to ameliorate AD. In this study, we assessed the effects of exercise on cognition and inflammation and studied the role of miR-148a-3p in AD. In 88 patients with AD, the expression of miR-148a-3p was studied using qRT-PCR. ROC curve and Pearson analysis were utilized to evaluate the roles of miR-148a-3p in AD. MWM test was conducted to investigate the effects of miR-148a-3p and exercise on cognition and memory. Moreover, inflammatory indicators were identified using an enzyme-linked immunosorbent assay. Relative luciferase levels reflected whether miR-148a-3p targeted SYNJ1. miR-148a-3p levels declined in patients with AD, indicating its potential as a biomarker. Interestingly, miR-148a-3p levels were elevated in patients with AD after exercise. MiR-148a-3p levels correlated with cognitive scores and proinflammatory levels. The cognitive situation and pro-inflammatory state were partly recovered in the mice after exercise. MiR-148a-3p silencing reversed these abovementioned tendencies. Patients with AD exhibited a low level of miR-148a-3p, which was increased after exercise. Therefore, exercise might improve the cognitive function and memory of mice with AD by upregulating miR-148a-3p.